2019
DOI: 10.1371/journal.pone.0219292
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription recombinase polymerase amplification assay for rapid detection of canine associated rabies virus in Africa

Abstract: Rabies is a neglected disease mostly affecting the developing world. Accurate and reliable diagnostic and surveillance data forms the foundation for the formulation and monitoring of control strategies. Although various sensitive and specific tests are available for detection of rabies virus, implementation of these tests in low-resource settings are challenging and remains limited. In this study, we describe the developed of a reverse transcription recombinase polymerase amplification assay for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Nevertheless, a highly sensitive RT-RPA for rapid detection of RABV was successfully established, exhibiting a reliable detection until 4 RNA molecules/reaction within 10 min. The RABV-RPA displayed only a 1-log 10 -step reduction compared to the reference standard RT-qPCR assay 19 and is more sensitive than the Schlottau assay (1000 RNA molecules/ reaction) 21 and a recently described RT-RPA assay (562 RNA molecules/reaction) 44 . In addition, obtaining results between 2 to 10 min demonstrated that the RABV-RPA assay is also much faster than the previously described rabies virus isothermal molecular tests 21,[45][46][47][48] without affecting the sensitivity.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, a highly sensitive RT-RPA for rapid detection of RABV was successfully established, exhibiting a reliable detection until 4 RNA molecules/reaction within 10 min. The RABV-RPA displayed only a 1-log 10 -step reduction compared to the reference standard RT-qPCR assay 19 and is more sensitive than the Schlottau assay (1000 RNA molecules/ reaction) 21 and a recently described RT-RPA assay (562 RNA molecules/reaction) 44 . In addition, obtaining results between 2 to 10 min demonstrated that the RABV-RPA assay is also much faster than the previously described rabies virus isothermal molecular tests 21,[45][46][47][48] without affecting the sensitivity.…”
Section: Discussionmentioning
confidence: 87%
“…In detection of clinical samples, the RT-RPA assay has a certain probability to produce false-negative results [32]. To improve the clinical sensitivity of RT-RPA, investigation into the influence of the amount and distribution of mismatches on RPA and the employment of degenerate primers [33] is in need. Besides, with better fluorescence detection equipment, this technique can be integrated into a phone-size portable device and be easily used for field detection in SFTS-prevalent areas.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RPA, an isothermal alternative of polymerase chain reaction (PCR), is a sensitive molecular diagnostic technology, which is rapid, portable, and can be multiplexed for several pathogens (Rostron et al, 2019 ). RPA has been used as reliable and rapid diagnostics for several viruses such as the human immunodeficiency virus (Crannell et al, 2014 ), Zika virus (Vasileva Wand et al, 2019 ), avian influenza A (Waheda et al, 2015 ), rabies virus (Coertse et al, 2019 ), Potato virus Y and Wheat dwarf virus (Glais and Jacquot, 2015 ), Tomato yellow leaf curl virus (Londoño et al, 2016 ), Apple stem grooving virus (Kim et al, 2018 ), and Banana bunchy top virus (Kapoor et al, 2017 ). Although these techniques proved better POCT techniques, detailed analysis of these molecular diagnostic mechanisms shows their low sensitivity and low throughput (Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%